Technological Innovation in the Olive Oil Production Chain - Muzzalupo, Innocenzo (IntechOpen, 2019)
Technological innovation has undergone unprecedented development; this evolution can offer extraordinary opportunities for product qualification, which today has not been adequately exploited due to a lack of vision. It took a disaster such as "mad cow" disease to accelerate the traceability plan; today, 36% of the analyzed agri-food companies, thanks to digital solutions, achieved a reduction in the times and costs connected with harvest processes, data management, and transmission. Digital solutions permit interventions aimed at food safety along the food chain, thus avoiding financial damage. But they can also be used to combat counterfeiting to protect the Protected Designation of Origin (PDO) and Protected Geographical Indication (PGI) systems for greater information for the consumer.